A CRITICAL APPRAISAL OF RELIGION AS A TOOL FOR VIOLENCE BY STATE AND NON-STATE ACTORS - Abraham Lubem Abado; Ogaba Solomon Isenyo (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
There's no gainsaying that the negative dimensions and the influence of various religions on humanity today is worrisome because most religions if not all, preaches peace, Justice and Equality, yet, same religions are used to fan embers of disunity amongst the people of our world. As seen in the various extremist attacks going on in our contemporary societies. Looking at the rise of various religious sects against one another and the society in general, some disturbing questions come to mind; ''What is the very essence of religion? If religion preaches peace, what then, is the interplay between religion and violence? In an attempt to answer these questions, hence the birth of this research. The research uncovered that the very foundations in which most religions for example Islam and Christianity was built have been perverted over time due to human selfish desires. The research however recommends that there's a need for all State and Non-state Actors to properly trace back to the very essence and foundations on which each religion was built to enhance the culture of religious tolerance amongst various religious sects.